2006
DOI: 10.1111/j.1600-0749.2006.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Mitf promoter by lipid‐stimulated activation of p38‐stress signalling to CREB

Abstract: The microphthalmia-associated transcription factor Mitf plays a critical role in regulating many aspects of melanocyte biology. It is required for melanoblast and postnatal melanocyte survival, regulates proliferation, and activates genes associated with differentiation such as tyrosinase and related genes involved in melanogenesis. Identifying the signals that regulate Mitf expression is crucial if we are to understand how cells of the melanocyte lineage respond to environmental cues. Here we show that the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 56 publications
2
133
1
4
Order By: Relevance
“…We also found that BMP6 induced MITF and TYR mRNA expression in MC, was blocked by the p38MAPK inhibitor, validating our view that p38MAPK plays an important role in BMP6-induced melanogenesis, and concurs with previous reports that BMPs stimulate MITF and TYR protein expression in chick embryo retinal pigment epithelium (Müller et al, 2007). Stress signalling, mediated via p38MAPK phosphorylation, is known to result in a rapid and persistent phosphorylation of Ser307 of MITF, which we and others have shown to be responsible for the transcription of genes involved in MC differentiation, proliferation and survival (Mansky et al, 2002;Vance and Goding, 2004;Saha et al, 2006). Furthermore, UVR-induced activation of stress-responsive p38MAPK can also lead to the phosphorylation of the ubiquitous bHLH-LZ transcription factor, USF-1, and like MITF this can bind and activate the TYR promoter in human MC (Galibert et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that BMP6 induced MITF and TYR mRNA expression in MC, was blocked by the p38MAPK inhibitor, validating our view that p38MAPK plays an important role in BMP6-induced melanogenesis, and concurs with previous reports that BMPs stimulate MITF and TYR protein expression in chick embryo retinal pigment epithelium (Müller et al, 2007). Stress signalling, mediated via p38MAPK phosphorylation, is known to result in a rapid and persistent phosphorylation of Ser307 of MITF, which we and others have shown to be responsible for the transcription of genes involved in MC differentiation, proliferation and survival (Mansky et al, 2002;Vance and Goding, 2004;Saha et al, 2006). Furthermore, UVR-induced activation of stress-responsive p38MAPK can also lead to the phosphorylation of the ubiquitous bHLH-LZ transcription factor, USF-1, and like MITF this can bind and activate the TYR promoter in human MC (Galibert et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is also notable that one of the top 6-mers (ranked fourth) is predicted to bind PAX3, a key regulator of melanocyte differentiation (Lang et al 2005) which can cause Waardenburg syndrome type 1 and type 3 when mutated (OMIM:193500 and OMIM:148820, respectively). In addition, CREB1, SOX5, and RUNX-family TFs (predicted to bind 6-mers ranked fifth, eighth, and ninth, respectively) have been shown to play roles in regulating gene expression in melanocytes (Tada et al 2002;Raveh et al 2005;Saha et al 2006;Kingo et al 2008;Stolt et al 2008;Kanaykina et al 2010;Mizutani et al 2010).…”
Section: Machine Learning Reveals Sequence Features That Underlie Melmentioning
confidence: 99%
“…33) The activation of this pathway induced the phosphorylation of CREB, resulting in the expression of TYR, TRP-1, and DCT genes. 34) As the data showed in Fig. 1F, 5-HT treatment for 120 min induced CREB phosphorylation, while IFN-γ has no obvious effect on CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 52%